Literatur Review: Pengaruh Karakteristik Komite Audit terhadap Audit Report Lag Perusahaan di Indonesia - Angelika Karonavita Boyani (Prosiding, 2026)
This study aims to systematically examine the influence of audit committee characteristics on audit report lag through a literature review of twelve academic articles published between 2021 and 2026. The three main audit committee characteristics examined include financial expertise, size, and meeting frequency. The results indicate that the financial expertise of the audit committee tends to have a significant effect in shortening the duration of audit report lag. Regarding the size of the audit committee, findings vary across studies; while most studies identify a significant effect, the direction of this effect varies depending on the industry context under examination. Meanwhile, the frequency of audit committee meetings shows an inconsistent pattern, with some studies finding a negative effect and others finding no effect on audit report lag.